2015
DOI: 10.3835/plantgenome2014.08.0037
|View full text |Cite
|
Sign up to set email alerts
|

Southern‐by‐Sequencing: A Robust Screening Approach for Molecular Characterization of Genetically Modified Crops

Abstract: Molecular characterization of events is an integral part of the advancement process during genetically modified (GM) crop product development. Assessment of these events is traditionally accomplished by polymerase chain reaction (PCR) and Southern blot analyses. Southern blot analysis can be time-consuming and comparatively expensive and does not provide sequence-level detail. We have developed a sequence-based application, Southernby-Sequencing (SbS), utilizing sequence capture coupled with nextgeneration seq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
72
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 65 publications
(72 citation statements)
references
References 41 publications
0
72
0
Order By: Relevance
“…Over 100 T0 RMCE events, were subjected to SbS analysis (Zastrow‐Hayes et al ., ). Only events with fully intact donor DNA insertions (flanked by intact FRT 1 / 87 sites) and no unintended DNA sequence were considered SbS‐pass events.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…Over 100 T0 RMCE events, were subjected to SbS analysis (Zastrow‐Hayes et al ., ). Only events with fully intact donor DNA insertions (flanked by intact FRT 1 / 87 sites) and no unintended DNA sequence were considered SbS‐pass events.…”
Section: Resultsmentioning
confidence: 97%
“…This design is similar to one described for soybean SSI (Li et al, 2009(Li et al, , 2010. The RTLs were molecularly characterized using Southern-by-Sequencing TM technology, hereafter referred to as SbS analysis (Zastrow-Hayes et al, 2015). SbS utilizes capture-based target enrichment of samples prior to next-generation sequencing (NGS) and is used to determine the insertion sequence and intactness of the inserted DNA at the target site.…”
Section: Development and Characterization Of Recombinant Target Linesmentioning
confidence: 99%
See 1 more Smart Citation
“…Among high-throughput sequencing technologies, SBS has long been used for molecular biology for more than a decade. It is relatively mature enough for routine work and several investigations for practical applications of this method have been carried out for GMOs [11][12][13][14][15][16] . In this study, we showed that in addition to past conventional methods, SBS is also immediately applicable to GEAP regulation.…”
Section: Discussionmentioning
confidence: 99%
“…In a recent study, using this approach, three 70 nucleotides long biotinylated probes were designed to target the extremities of T-DNA sequences to rapidly locate the T-DNA insertion sites in 55 out of 64 mutant Arabidopsis plants [259]. A similar approach, called Southern-by-Sequencing (SbS), was used to characterise the insertion sites in GM crops [260]. In both the approaches, information of the construct close to the insertion sites is necessary for characterisation, which is typically not the case in unknown GMO identification.…”
Section: Probe Hybridisation Approachmentioning
confidence: 99%